2014
DOI: 10.1073/pnas.1411765111
|View full text |Cite
|
Sign up to set email alerts
|

Size limits of self-assembled colloidal structures made using specific interactions

Abstract: We establish size limitations for assembling structures of controlled size and shape out of colloidal particles with short-ranged interactions. Through simulations we show that structures with highly variable shapes made out of dozens of particles can form with high yield, as long as each particle in the structure binds only to the particles in their local environment. To understand this, we identify the excited states that compete with the ground-state structure and demonstrate that these excited states have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
90
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 42 publications
1
90
0
Order By: Relevance
“…The typical self-assembly paradigm encodes information through the specific interactions between building blocks that in turn promote assembly. For example, a given amino acid sequence consistently folds into a specific protein structure, and DNA-coated colloids can be designed with specific interactions so that a desired structure is the thermodynamic ground state (13)(14)(15). Our approach differs in that the information for assembly is not coded directly into the building blocks but is instead encoded in the active colloids, which serve as a microscopic assembly machine.…”
mentioning
confidence: 99%
“…The typical self-assembly paradigm encodes information through the specific interactions between building blocks that in turn promote assembly. For example, a given amino acid sequence consistently folds into a specific protein structure, and DNA-coated colloids can be designed with specific interactions so that a desired structure is the thermodynamic ground state (13)(14)(15). Our approach differs in that the information for assembly is not coded directly into the building blocks but is instead encoded in the active colloids, which serve as a microscopic assembly machine.…”
mentioning
confidence: 99%
“…On the other hand, a cluster is characterized by the species of particles that comprise it, where the species of two particles determines the specific interaction between them. The number of different species of particles is not necessarily the same as N. It has been previously established how specific interactions can be chosen for any given geometry (8,16,24,25) and how self-assembly yield of clusters depends on the chosen interactions (8,24). In the present work, we do not consider self-assembly of clusters in a bath of particles (8,16,25,26); however, our ability to enumerate cluster geometries and choose interactions to stabilize any desired cluster is a critical ingredient for the discoveries reported here.…”
Section: Resultsmentioning
confidence: 99%
“…These stickers cause short-ranged, specific interactions between particles, with a programmable binding strength between pairs of particles. We have recently shown that this system has the potential of allowing high-yield equilibrium self-assembly of large structures, up to 1,000 particles (8). Classical experiments showed that DNA-based specific interactions allow assembly of crystals of nanoparticles (9)(10)(11)(12).…”
mentioning
confidence: 99%
“…Such predictions are especially valuable, given the proliferation of different mechanisms for creating and combining distinct mechanisms of specificity: Mutual information provides an unbiased way of comparing their efficacy to each other. As programmable specificity continues to drive technological developments in self-assembly (41), understanding how the mutual information of paired components can be built up toward creating larger, multicomponent objects is a critical future direction of this work.…”
Section: Discussionmentioning
confidence: 99%